Gas-phase oxidation of methyl crotonate and ethyl crotonate. Kinetic study of their reactions toward oh radicals and Cl atoms - Teruel, Mariano Andres (2012)
Rate coefficients for the reactions of hydroxyl radicals and chlorine atoms with methyl crotonate and ethyl crotonate have been determined at 298 K and atmospheric pressure. The decay of the organics was monitored using gas chromatography with flame ionization detection (GC-FID), and the rate constants were determined using the relative rate method with different reference compounds. Room temperature rate coeficcients were found to be (in cm 3 molecule -1 s -1): k 1(OH + CH 3CH=CHC(O)OCH 3) = (4.65 ± 0.65) × 10 -11, k 2(Cl + CH 3CH=CHC(O)OCH 3) = (2.20 ± 0.55) × 10 -10, k 3(OH + CH 3CH=CHC(O)OCH 2CH 3) = (4.96 ± 0.61) × 10 -11, and k 4(Cl + CH 3CH=CHC(O)OCH 2CH 3) = (2.52 ± 0.62) × 10 -10 with uncertainties representing ±2σ. This is the first determination of k 1, k 3, and k 4 under atmospheric pressure. The rate coefficients are compared with previous determinations for other unsaturated and oxygenated VOCs and reactivity trends are presented. In addition, a comparison between the experimentally determined k OH with k OH predicted from k vs E HOMO relationships is presented. On the other hand, product identification under atmospheric conditions has been performed for the first time for these unsaturated esters by the GC-MS technique in NO x-free conditions. 2-Hydroxypropanal, acetaldehyde, formaldehyde, and formic acid were positively observed as degradation products in agreement with the addition of OH to C2 and C3 of the double bond, followed by decomposition of the 2,3- or 3,2-hydroxyalkoxy radicals formed. Atmospheric lifetimes, based on of the homogeneous sinks of the unsaturated esters studied, are estimated from the kinetic data obtained in the present work.